The Use of Mobile Educational Tools to Improve Antimicrobial Prescription for the Treatment of Acute Pyelonephritis in Pregnancy: A Retrospective Cross-sectional Study - Antonello, Vicente Sperb; Cunegatto, Marjane Caroline; Rosin, Elisa Tasca; Castilhos, Júlia Xavier; Beduschi, Fabrícia Gamba; Bumaguin, Daniela Benzano; Antonello, Ivan Carlos Ferreira; Jimenez, Mirela Foresti (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective To analyze the prescription of antimicrobial agents for pregnant women admitted into the obstetrics service who presented with acute pyelonephritis.Methods Three cross-sectional studies were performed comparing the prescription of antimicrobials for pyelonephritis in pregnant women in the time periods evaluated (2010–2011: 99 patients evaluated; 2013: 116 patients evaluated; 2015: 107 patients evaluated), at the Hospital Fêmina, Porto Alegre, in the state of Rio Grande do Sul, Brazil. The analysis was performed before and after the promotion of an institutional protocol for the treatment of pyelonephritis during pregnancy, and on a third occasion after the introduction of a smartphone-based mobile educational tool.Results The evaluation of the prescribing physicians and the adequacy of the prescriptions between the different periods studied revealed a significant increase in appropriate conduct for the choice of antimicrobial (2010: 83.8%; 2013: 95.7%; and 2015: 100%), route of administration (2010: 97%; 2013: 100%; and 2015: 100%), and interval (2010: 91.9%; 2013: 95.7%; and 2015: 100%), following the introduction of the protocol, and again after the implementation of the software application with orientations on the antimicrobial treatment.Conclusion The use of specific mobile applications should be encouraged to attain a better quality and accuracy in prescriptions and to include strategies that not only reduce the risk of negative outcomes, but also improve the quality of care and treatment for maintaining the health both of the mother and of the baby.
Keywords: urinary tract infections; pregnancy; medical education; medical informatics application